Pengaruh Perawatan Payudara terhadap Kadar Prolaktin dan Volume ASI pada Ibu Postpartum Primipara - Siti Lestari; Yusri Dianne Jurnalis; Fadil Oenzil (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2022)
Abstract BackgroundExclusive breast milk is breastfeeding for infants from 0-6 months in order to meet the nutritional needs for growth and development. Breastfeeding has unmatched advantages for infants, mothers, families and communities. It is strongly recommended to exclusively breastfeed for 6 months. The production and excretion of breast milk is influenced by the prolactin hormone and the oxytocin hormone. ObjectiveProlactin affects the amount of milk produced. Breast care is highly important; one of which is maintaining breast hygiene, especially the hygiene of the nipples to avoid infection and to soften it, so that the infant can be breastfed properly, and stimulates the glands.Method an experimental research with post test only control group design in Andalas Community Health Center, Padang. The sample in this study consisted of 15 treatment groups and 15 control groups that met the inclusion criteria taken by simple random sampling technique. Breast care was carried out on the third trimester of pregnant women starting from the age of 34 weeks carried out three times a week. Prolactin level was measured by ELISA and breastmilk volume was measured by measuring tubes. The normality test used the Shapire Wilk test. Statistical test used independent t test.Results and DiscussionThe results of this study indicated that the mean of prolactin level in the breast care group (425,00 ± 41,08) was greater than the control group (372,34 ± 43,59). The results of statistical tests revealed that there was a significant effect of breast care on prolactin level (p = 0,002). Besides, the volume of breast milk in the breast care group was (32,67 ± 4,60) greater than the control group (26,60 ± 4,29). The results of statistical tests showed that there was a significant effect of breast care on breast milk volume (p = 0,001).ConclusionProlactin level and milk volume in postpartum primiparous mothers who did breast care were more in production than mothers who did not do breast care and the difference was significant.